The impact of problem solving games using balls in the development of some of the basic movements for nine years old - Raheem, Waad (Journal of Physical Education, 2012)
The research aims to identify the impact of problem solving games using balls in the development of some of the basic movements for nine years old boys. The sample include twenty students from (Alshabaat ) primary school from the third grade, They were randomly selected and divided into two groups ; control group and experimental group and each group include ten students, The items of program made by ministry of education were applied on students of the control group and program made by researcher was applied on students of experimental group, The researcher used the Ohio State University to evaluate the basic movements, and after giving the prescribed curriculum was testing dimensional imaging videos and editing and transfer of imaging to CD (DVD) and given to the evaluators of the four to assess the basic movements, and after receiving the evaluation results, the researcher "extract the score of each test by writing off Class the highest and lowest given by the four referees and the average degree, The researcher concluded that the differences in the dimensional measurement of all the basic movements and was in favor of the experimental group.